Do all patients in the epilepsy monitoring unit experience the same level of comfort? A quantitative exploratory secondary analysis. (27th November 2021) - Egger‐Rainer, Andrea; Hettegger, Sophie Martina; Feldner, Raphael; Arnold, Stephan; Bosselmann, Christian; Hamer, Hajo; Hengsberger, Anna; Lang, Johannes; Lorenzl, Stefan; Lerche, Holger; Noachtar, Soheyl; Pataraia, Ekaterina; et al.
Abstract: Aims: To find out which variables may be associated with comfort of patients in an epilepsy monitoring unit. Design: Exploratory, quantitative study design. Methods: Data were collected from October 2018 to November 2019 in Austria and Southern Germany. A total of 267 patients of 10 epilepsy centres completed the Epilepsy Monitoring Unit Comfort Questionnaire which is based on Kolcaba's General Comfort Questionnaire. Secondary data analysis were conducted by using descriptive statistics and an exploratory model building approach, including different linear regression models and several sensitivity analyses. Results: Total comfort scores ranged from 83 to 235 points. Gender, occupation and centre turned out to be possible influential variables. On average, women had a total comfort score 4.69 points higher than men, and retired persons 28.2 points higher than high school students ≥18 years. Comfort scores of younger patients were lower than those of older patients. However, age did not show a statistically significant effect. The same could be observed in marital status and educational levels. Conclusion: When implementing comfort measures, nurses must be aware of variables which could influence the intervention negatively. Especially, high school students ≥18 years should be supported by epilepsy specialist nurses, in order to reduce uncertainty, anxiety and discomfort. But, since the identified variables account only for a small proportion of the inter‐individual variability in comfort scores, further studies are needed to find out additional relevant aspects and to examine centre‐specific effects more closely. Impact: Nurses ensure patient comfort during a hospital stay. However, there are variables that may impair the effectiveness of the nursing measures. Our study showed that the experience of comfort was highly individual and could be explained by sociodemographic variables only to a limited extent. Nurses must be aware that additional factors, such as the situation in the individual setting, may be relevant.